Chondroid metaplasia: a rare subtype of metaplastic breast carcinoma - Demirli Atıcı, Semra; Salimoğlu, Semra; Kırmızı, Yasemin; Kuzukıran, Dilek; Aydın, Cengiz (The European Research Journal, 2020)
Metaplastic breast carcinoma (MBC) is a subtype of breast malignant lesions which is very rare seen. Clinically, MBC is more aggressive and has worse prognosis than other subtypes of breast cancers. A 61-year-old female patient who had a rapidly enlarging and palpabl  mass on the left breast applied. Core biopsy was performed and pathology was reported as  invasive ductal carcinoma. The patient who had been diagnosed with breast cancer was  operated and postoperative course was unremarkable. She was discharged postoperative third day with no complication. Postoperative specimen pathology was reported as a rare type of  breast metaplastic carcinoma which was chondroid metaplasia. Here we aimed to report, a case of chondroid metaplasia which is a rare type of metaplastic breast carcinoma with the literature.